Sosial Hukum dan Keadilan Untuk Semua: Menggugah Kesadaran Hukum pada Masyarakat Cahaya Negeri - Romanza, Melli; Eceh Trisna Ayuh; Titi Darmi (JURNAL ABDIMAS SERAWAI, 2024)
Legal awareness within society is a key factor in establishing a just and orderly social structure. Unfortunately, in Indonesia, legal awareness remains relatively low, as reflected in the frequent legal violations occurring in both private and public spheres. The program "Law and Justice for All: Raising Legal Awareness in Society" aims to enhance public understanding of their legal rights and obligations, as well as the crucial role law plays in achieving social justice.This program includes various activities such as seminars, panel discussions, legal awareness campaigns, free legal clinics, and paralegal training, all designed to provide practical and easily applicable legal education for the wider community. The goal is not only to improve legal knowledge but also to change societal behavior to foster greater respect for and adherence to the law.With an inclusive educational approach, the program is aimed at the general public, encouraging active participation in law enforcement and reducing legal violations. Ultimately, higher legal awareness is expected to form the foundation for a more just and harmonious society.